2014
DOI: 10.4103/1596-3519.142291
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and outcome of admissions in the medical wards of a tertiary health center in a rural community of Ekiti state, Nigeria

Abstract: Male gender and elderly aged groups were predominant on admission. Noncommunicable diseases were of higher proportion on admission than communicable diseases. The most common cause of death was cardiovascular diseases of which stroke topped the list.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
29
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 26 publications
11
29
2
Order By: Relevance
“…The rate of improved and discharged patients (78.0%) was similar to the rate reported in a tertiary health centre in Nigeria, but lower than rates reported from hospitals in Ethiopia and Sudan. 1,6,18 In most cases, the average duration of hospital stay in the current study was one week or less (86.3%), which is consistent with similar studies carried out in Khartoum and Pakistan. 6,15 This could be explained by the fact that most acute communicable diseases, as well as uncomplicated NCDs, are treatable within this short timeframe.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The rate of improved and discharged patients (78.0%) was similar to the rate reported in a tertiary health centre in Nigeria, but lower than rates reported from hospitals in Ethiopia and Sudan. 1,6,18 In most cases, the average duration of hospital stay in the current study was one week or less (86.3%), which is consistent with similar studies carried out in Khartoum and Pakistan. 6,15 This could be explained by the fact that most acute communicable diseases, as well as uncomplicated NCDs, are treatable within this short timeframe.…”
Section: Discussionsupporting
confidence: 80%
“…1,18 This low mortality rate may, in part, reflect the comprehensive health services offered at Atbara Teaching Hospital. The most commonly reported causes of death (sepsis, stroke and renal failure) could likewise be explained by the high prevalence of hypertension and diabetes mellitus and the high percentage of older subjects in the current study population.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the present study, a Nigerian study showed cardiovascular diseases to be most frequent reason for hospital admission with cardiovascular system being involved in 32% of cases [19]. Similar results were found in studies conducted in Australia and Hong Kong which reported cardiovascular system being involved in 29% and 30.3% of cases admitted to medical ward respectively [20].…”
Section: Discussionsupporting
confidence: 74%
“…Several other studies from different parts of the developing world have shown similar results of a shift in the disease pattern responsible for admission toward cardiovascular diseases [3,4]. …”
Section: Discussionmentioning
confidence: 53%
“…The Saudi Arabian health care system is ranked among the best in the Middle East region [4]. However, burden of disease and causes of hospitalization and death within the community remains largely unknown from most parts of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%